2006
DOI: 10.1016/j.rmed.2006.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural investigation of epithelial damage in asthmatic and non-asthmatic nasal polyps

Abstract: Nasal polyposis is a poorly understood chronic inflammatory disease often associated with asthma. As nasal polyps and asthma both are associated with massive eosinophil infiltration, they may share a common pathophysiological mechanism. Many genetic and autoimmune diseases may result from altered expression or function of cell adhesion molecules such as desmosomes. A transmission electron microscopical study was carried out on tissue from 15 patients suffering from nasal polyps, to investigate if there are cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 47 publications
0
31
0
Order By: Relevance
“…29 In addition, a loss of desmosomal length, important for adhesion and barrier function of epithelium, has been shown in nasal polyps. 30 The significant reduction in expression of epithelial factors known to be involved in mechanical and innate immune barrier functions, S100A7 and SPINK5, raises potential mechanisms for the epithelial damage previously reported in nasal polyposis. As established by IHC, the protein encoded by SPINK5 expression is present in the upper airways and is reduced in CRSwNP, in particular within nasal polyps themselves.…”
Section: Discussionmentioning
confidence: 96%
“…29 In addition, a loss of desmosomal length, important for adhesion and barrier function of epithelium, has been shown in nasal polyps. 30 The significant reduction in expression of epithelial factors known to be involved in mechanical and innate immune barrier functions, S100A7 and SPINK5, raises potential mechanisms for the epithelial damage previously reported in nasal polyposis. As established by IHC, the protein encoded by SPINK5 expression is present in the upper airways and is reduced in CRSwNP, in particular within nasal polyps themselves.…”
Section: Discussionmentioning
confidence: 96%
“…Those observations together with the other characteristics of airway remodeling were found not only in severe chronic asthma cases, but also in the airways of pediatric patients in relation to the disease onset [4][5][6]. Airway epithelium is chronically injured and unable to repair properly in asthmatic patients [7,8] and the epithelial cell layer is more fragile due to the disruption of tight junctions and desmosomes [6,9]. This results in the increased permeability, making airways more accessible to inhaled allergens, pollutants and other irritants (e.g.…”
Section: Introductionmentioning
confidence: 83%
“…Zuckerman et al [4] investigated desmosomal DSG2 and DSG3 in nasal polyposis patients and control subjects and found that the expression of both DSG2 and DSG3 was significantly decreased in nasal polyps compared with the control mucosa. Similarly, another study investigating ultrastructural epithelial damage in nasal polyps from asthmatic and/or allergic patients versus non-asthmatic and non-allergic patients showed that the relative length of columnar cell or basal cell desmosomes was reduced in patients with asthma or allergy compared to non-allergic and non-asthmatic patients [12]. This suggests that there may be a weakness in the desmosomes of subjects with an allergic disease.…”
Section: Discussionmentioning
confidence: 99%
“…inflammatory bowel disease [25], allergic inflammation [26,27,28], viral infections [29,30] and asthma [12,31], one of our previous studies showed that herpes simplex virus and Staphylococcus aureus could invade the nasal mucosa through the intercellular space of epithelial cells [32]. We have tried to examine the expression of the five most representative epithelial intercellular junctional proteins in the sinonasal mucosa of patients with CRS according to the degree and type of inflammation in these individuals.…”
Section: Discussionmentioning
confidence: 99%